"Systems Engineering helping to raise public awareness". Issue 1 (13th September 2016) - TERRIEN, Olivier
Abstract: Oty Productions SAS is a French company specialized in raising awareness and popularizing technical domains. Until 2013, Project Management was classical and mainly chronological. When we decided to develop a project with a new illustrated book, we adopted concepts and tools proposed by the INCOSE. Written as a testimony, this paper demonstrates their possible translation into a 'raising awareness' problem. Based on a project named "Crow versus Crow", this paper shows notions and methods applied during the engineering phase of a system addressing a non‐initiated and young audience about Electronics which is everywhere in today's life. This document describes how these tools were used in the realm of books and conferences. It shows achieved results through this way of proceeding and compares them to those of previous projects. Since this systematic approach in an unusual field of application for the INCOSE was relevant and successful, this paper lays the foundations of our next project for years to come. Convinced of these principles and practices, Oty Productions has started a project to raise awareness about systems and to popularize their engineering processes.